2019
DOI: 10.1042/bsr20192196
|View full text |Cite
|
Sign up to set email alerts
|

Trimeric heptad repeat synthetic peptides HR1 and HR2 efficiently inhibit HIV-1 entry

Abstract: The trimeric heptad repeat domains HR1 and HR2 of the human immunodeficiency virus 1 (HIV-1) gp41 play a key role in HIV-1-entry by membrane fusion. To develop efficient inhibitors against this step, the corresponding trimeric-N36 and C34 peptides were designed and synthesized. Analysis by circular dichroism of monomeric and trimeric N36 and C34 peptides showed their capacities to adopt α-helical structures and to establish physical interactions. At the virological level, while trimeric-C34 conserves the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…However, these domains play crucial roles during the process of fusion [28][29][30][31][32]. Overall, these findings indicate that GTEs may have their own complex evolutionary history, which involves multiple internal recombination events of different regions and results in the observed diversity.…”
Section: Discussionmentioning
confidence: 81%
“…However, these domains play crucial roles during the process of fusion [28][29][30][31][32]. Overall, these findings indicate that GTEs may have their own complex evolutionary history, which involves multiple internal recombination events of different regions and results in the observed diversity.…”
Section: Discussionmentioning
confidence: 81%
“…Interaction between three HR1 and HR2 domains of the trimeric fusion protein, leads to the formation of the 6-HB, which is critical for bringing the viral and host membranes in close proximity, hence driving their fusion ( 6 , 8 , 30–32 ). This makes the 6-HB structure an attractive drug target for blocking membrane fusion and viral entry ( 11–15 , 33–38 ). However, till date, the 6-HB structure has been mostly targeted using long peptides (35 to 50 amino acids) mimicking either HR1 or HR2 helices ( 11 , 13 , 39–41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The V3 region is integrally involved in both receptor binding and the determination of viral tropism 33,34 . The CH2 terminal region plays a key role in HIV-1 entry by membrane fusion 35 . When we compared the enrichment of these envelope peptides between NS and AS escape subjects, we found that AS escape subjects more highly enriched the CH2 terminal epitope relative to NS escape subjects.…”
Section: Discussionmentioning
confidence: 99%